SUCCESSFUL TREATMENT OF A PATIENT WITH SEVERE DEFEAT OF THE KNEE - V. D. Sikilinda; A. V. Alabut; A. V. Bondarenko (Медицинский вестник Юга России, 2013)
The case of successful treatment of the patient with heavy post-traumatic osteoartrosis of the knee joint, being combined with damage of the muscles extensori of the knee joint (EMKJ) is presented. Two-stage surgical intervention is executed. The first stage – combined alloplastic and autoplastic a defect of a muscle quadriceps of the hip, EMKJ restoration. The second stage – a total arthroplasty of the left knee joint an oncological prothesis. At an assessment of the remote results of the Oxford scale for a knee joint the results of the knee joint arthroplasty is estimated as excellent in 12 months at 23 points, in 24 and 36 months in 12 points.